2011
DOI: 10.1093/ndt/gfq843
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal initiation of dialysis with and without early referral to a nephrologist

Abstract: Suboptimal initiation of dialysis is common in patients referred early or late. The benefits of early referral are lost if dialysis is initiated suboptimally. There is a need to identify factors that lead to suboptimal initiation despite early referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
148
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(163 citation statements)
references
References 29 publications
9
148
2
4
Order By: Relevance
“…These factors are especially important for older adults, because they suffer a greater burden of comorbid illness compared with their younger counterparts, 30 often progress to ESRD after episodes of AKI, 31 and may be more likely than younger persons to initiate dialysis under suboptimal circumstances (e.g., emergent inpatient settings). 32 In our study, we identified previously unreported independent risk factors for early dialysis initiation (CHF hospital admissions and all-cause hospitalization days in the 6 months preceding initiation) and found that the consideration of these factors and other predialysis factors served to attenuate, at least somewhat, the risk of poor outcomes associated with early initiation.…”
Section: Discussionmentioning
confidence: 62%
“…These factors are especially important for older adults, because they suffer a greater burden of comorbid illness compared with their younger counterparts, 30 often progress to ESRD after episodes of AKI, 31 and may be more likely than younger persons to initiate dialysis under suboptimal circumstances (e.g., emergent inpatient settings). 32 In our study, we identified previously unreported independent risk factors for early dialysis initiation (CHF hospital admissions and all-cause hospitalization days in the 6 months preceding initiation) and found that the consideration of these factors and other predialysis factors served to attenuate, at least somewhat, the risk of poor outcomes associated with early initiation.…”
Section: Discussionmentioning
confidence: 62%
“…Patients treated with HHD tend to be younger, have less comorbidity, and have different etiologies of primary kidney disease (8,18,27,39). They are also less likely to have late nephrology referral, another factor associated with poor clinical outcomes (50)(51)(52). Although the previous factors can be addressed by statistical adjustment, other components, such as commitment to dialysis treatment, education level, psychologic skills, social support, and economic status, are much harder to account for, especially in a registry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-optimal initiation, as defined by Mendelssohn et al [1], is not a covariate recorded in the French Language Peritoneal Dialysis Registry. A period of <30 days on HD before PD initiation was considered as a proxy of the sub-optimal dialysis start.…”
Section: Definition Of the Variablesmentioning
confidence: 99%
“…The term sub-optimal dialysis initiation was recently proposed to describe the treatment of end-stage renal disease patients who started dialysis while hospitalized and/or through a dialysis catheter and/or not on their dialysis modality of choice [1]. The sub-optimal dialysis initiation is a common situation in patients starting renal replacement therapy even for those patients followed regularly in the pre-dialysis clinic [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation